2018
DOI: 10.1016/j.jmr.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced dipolar spectroscopy – A quantitative comparison between LiDEER and LaserIMD

Abstract: Nanometric distance measurements with EPR spectroscopy yield crucial information on the structure and interactions of macromolecules in complex systems. The range of suitable spin labels for such measurements was recently expanded with a new class of light-inducible labels: the triplet state of porphyrins. Importantly, accurate distance measurements between a triplet label and a nitroxide have been reported with two distinct light-induced spectroscopy techniques, (light-induced) triplet-nitroxide DEER (LiDEER)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…These effects have also been observed in some experimental data. 32,33 Note that experimental LaserIMD traces are typically recorded by moving the Hahn-echo sequence through a fixed laser flash, which results in a mirror inverted trace. As none of the three simulations for the photoexcitable spin labels showed major deviations from those of porphyrin, we concluded that RB, EO and AT12 are suitable labels for LaserIMD measurements.…”
mentioning
confidence: 99%
“…These effects have also been observed in some experimental data. 32,33 Note that experimental LaserIMD traces are typically recorded by moving the Hahn-echo sequence through a fixed laser flash, which results in a mirror inverted trace. As none of the three simulations for the photoexcitable spin labels showed major deviations from those of porphyrin, we concluded that RB, EO and AT12 are suitable labels for LaserIMD measurements.…”
mentioning
confidence: 99%
“…The first work in this area was conducted on a peptide-based molecular ruler containing a nitroxide probe and porphyrin moiety. [31][32][33] It was found that the relative signal-to-noise of the two techniques depends strongly on the degree of excitation that can be achieved by the pump pulse used in LiDEER, the laser excitation, the relative relaxation times of the two species being investigated and the inter spin distance range that needs to be probed. [29] The dipolar measurements were performed with light-induced DEER (LiDEER), [25,26] a variation of the conventional 4-pulse DEER sequence where a laser pulse is used to generate the triplet state before the application of dichromatic microwave pulses: the detection frequency is resonant with the photo-induced porphyrin triplet and the pump is resonant with the stable nitroxide radical.…”
mentioning
confidence: 99%
“…Additionally, for the first time, the LiRIDME sequence, in the five-pulse dead-time free version, is applied to a triplet probe providing evidence that the longitudinal relaxation properties of the triplet state can be favorable for the application of this technique. [31,32] RIDME has previously been shown to be more sensitive than DEER for measuring inter-spin interactions between paramagnetic species with different longitudinal (T 1 ) relaxation times and in the presence of broad EPR spectra. The ReLaserIMD data set is good, characterized by a modulation depth of 18 % and a signal to noise S/N ' 49.…”
mentioning
confidence: 99%
See 2 more Smart Citations